Analysis of the spatial heterogeneity and influencing factors of music training institutions: a case study of Beijing, Shanghai, Guangzhou, and Shenzhen - Jun Zhao; Xiangwen Cui; Shaohua Wang; Wenwen Liu; Jiewen Liu; Chang Liu; Yang Zhong; Zhidong Zhang (Computational Urban Science)
Abstract In contemporary society, music art plays a pivotal role in enhancing spiritual quality-of-life and optimizing talent cultivation models. The spatial distribution of music educational resources undoubtedly plays a promotional role in enhancing the quality of music education. However, existing research has not conducted specialized and in-depth studies on this topic. This study uses a geographic information system (GIS) and classical geographical research methods such as the nearest neighbor index, kernel density analysis, and geographic detectors to analyze the spatial distribution and influencing factors of music training institutions in Beijing, Shanghai, Guangzhou, and Shenzhen. The results indicate that the distribution of these institutions is obviously clustered, with a "northeast‒southwest" trend in Beijing and Shenzhen and a "northwest‒southeast" trend in Shanghai and Guangzhou. Among the categories of urban facilities, which encompass sports, leisure, shopping, and dining, sports venues exert the most substantial influence on the spatial distribution characteristics of music training institutions. The location of music training institutions should be closely integrated with the spatial distribution of urban facilities. This study provides theoretical foundations and practical guidance for policy-makers in the refined adjustment of urban layouts, the rational allocation of artistic educational resources, and the promotion of cultural industry development.